Informasi Hoax di Media Sosial Facebook - Melinda Wahyuni (Nuances of Indonesian Language, 2021)
This study aims to: (1) describe the structure of hoax on Facebook social media, (2) describe the contents of hoax messages on Facebook; and (3) describe the characteristics of using hoax in Facebook social media. This type of research is a qualitative descriptive study. This research was carried out on Facebook. Data collection was carried out during August 2019 - January 2020. The research design used was descriptive qualitative. The focus of this research is hoax information and hoax information disseminating accounts. Research data sources, namely hoax information disseminating facebook account. Data collection techniques are done by reading Facebook account posts, identifying hoax information, making screenshots or screenshoots, copying hoax-identified messages, verifying, determining hoax-categorized information, and analyzing based on data analysis guidelines. The research instrument consisted of the main instrument namely the researcher and the observation guide table. The results of the study reveal the structure, content of hoax messages, and the linguistic characteristics of hoax texts. The structure of the hoax text found consists of 10 patterns, namely (1) Recognition of issues, Reaffirmation, Series of arguments, and Statement of solicitation, (2) Statement of solicitation, Recognition of issues, Sequence of arguments, and Reaffirmation, (3) Recognition of issues, Sequence arguments and solicitation statements, (4) recognition of issues, series of arguments, and reaffirmation, (5) recognition of issues, invitation statements, and series of arguments, (6) recognition of issues and series of arguments, (7) recognition of issues, and solicitation of invitations , (8) solicitation statement and series of arguments, (9) introduction of the issue, and (10) solicitation statement. The contents of the message found consisted of 5 types, namely (1) scary hoax messages, (2) emotional hoax messages, (3) hoax messages full of promises, (4) encouraging messages, and (5) humorous messages. The linguistic characteristics found consist of 3 namely (1) the use of technical words, (2) the use of argumentative conjunctions, including (a) the use of the conjunction "if", (b) the use of the conjunction "cause", ( c) the use of the conjunctions "because", (4) the use of the conjunctions "so", (5) the use of the conjunctions "their consequences". (3) use of command sentences, including (a) viral (b) distribute.